Selection indices between agronomic and chemical traits in purple corn (Zea mays L.) hybrids in southern Sonora, Mexico - Rodríguez-Pérez, Gilberto (2023)
In Mexico, corn is considered the most important crop, 88% is planted with white corn, 11% yellow and 1% colored, blue or purple corns are rich for their nutritional properties as they contain anthocyanins, characterizing them as special for consumption human. The objective of this research was to estimate selection indices using agronomic and chemical traits in purple maize hybrids in southern Sonora, 19 hybrids and one Creole maize were evaluated in the field and in the laboratory, once the experiment was harvested, the seed was evaluated in the food laboratory of the TecNM-Valle del Yaqui, the agronomic variables were days to female flowering (FF), grain yield (GY), thousand grain weight (TW), hectoliter weight (HW), flotation index (FI), grains per row (GR), rows per ear (RE), ear length (EL), chemical: fat, ash, fiber, protein, carbohydrates and anthocyanins. The results showed statistical differences in all the variables, the selection indices allowed to identify the hybrids 19, 14, 7, 16, 18, 15, 9 and 10 for presenting minimum values ​​in all the simultaneous variables studied, they had the best yields, They were from a later cycle, presented higher PMG, had a smooth texture, special for making tortillas, also obtained the highest averages in fat, fiber, protein, anthocyanins and carbohydrates, which are favorable due to their nutritional properties, which will have beneficial and antioxidant effects that can benefit human health in different products derived from pigmented corn, these same hybrids were associated with more GH, RG, IF, PH, fat, fiber, protein and anthocyanins.